Pengaruh Massa Biosorben Kulit Batang Kayu Jawa (Lannea coromandelica) terhadap Kapasitas Adsorpsi Ion Cd(II) - Wulandari, Niken Cahyaning; Widwiastuti, Hanandayu; Yudhistia Asworo, Riska (JURNAL ATOMIK, 2023)
Cadmium is one of the heavy metals that can contaminate bottled drinking water (AMDK) and cause health problems if its concentration more than the maximum limit. According to SNI 01-3553-2006, the maximum concentration of cadmium in AMDK is 0.003 mg/L. An effective method to reduce Cd levels is adsorption. In this research, use material diversification by utilizing Java Bark as biosorbent. This is because the Java Bark contains tannin compounds that can bind heavy metals. One of the factor that can affect adsorption is biosorbent mass. The aims of study is determine the effect of Java Bark biosorbent mass to the adsorption capacity of Cd(II) by Atomic Absorption Spectrophotometry (AAS). Java Bark biosorbent mass used were 0.1; 0.5; 1; 1.5; and 2 g. The results showed that the biosorbent mass of 0.1 g had the largest adsorption capacity of 9.47 mg/g. Meanwhile, the adsorption capacity of the biosorbent mass of 0.5-2 g tends to decrease because the surface of the biosorbent has been saturated and particle aggregation so that Cd(II) desorption. From the results of the study, it can be concluded that the Java Bark biosorbent with a mass of 0.1 g has the largest adsorption capacity for adsorption Cd(II).